Assistive courseware for the visually impaired based on theory of multiple intelligence and SECI model - Aziz, Nurulnadwan; Mohamad Roseli, Nur Hazwan; Eshak, Erratul Shela; Abdul Mutalib, Ariffin (Science Publications, 2011)
Problem statement: Courseware is one of the educational aids in teaching and learning process. Nowadays, courseware together with multimedia elements is utilized to ease learners in grasping knowledge. However, the courseware for Visually-Impaired (VI) is yet to be developed. Approach: This study discusses the development of Assistive Courseware (AC) for visually impaired learners based on Theory of Multiple Intelligence (MI) and also adapt knowledge spiral model. It explains how the AC delivers knowledge to VI learners. The phases, design and development methods involved in the research are outlined. Results: Results showed that the AC is fully equipped with the eight types of MI theory and the use of SECI model in transferring knowledge between AC and VI learners has been proven. Conclusion: The AC has been proposed for the VI learners and observed on their reactions. Overall, the VI learners were vary positive upon the AC and was excited to learn with the AC. Next step of the study is not only to report on the findings from observation, but also to experiment the prototype with VI learners in terms of cognitive implications using empirical data.